Pengaruh Pembinaan Pengawas Sekolah, Kepemimpinan Kepala Sekolah Dan Sarana Prasarana Terhadap Kinerja Guru Tk Kapanewon Sewon Dengan Motivasi Kerja Sebagai Variabel Moderating - Hartinem, Hartinem; Pardimin, Pardimin (Media Manajemen Pendidikan, 2024)
The Effect of Supervision of School Supervisors, Principal Leadership and Infrastructure on the Performance of Teachers at Kapanewon Sewon Kindergarten with Work Motivation as a Moderating Variable. Thesis. Yogyakarta: Directorate of Postgraduate, Universitas Sarjanawiyata Tamansiswa Yogyakarta, 2022. This study aims to analyze the influence of the development of school supervisors, principal leadership, infrastructure and work motivation both simultaneously and partially on the performance of the teachers of the Kapanewon Sewon Kindergarten. This research was conducted at the Kapanewon Sewon Kindergarten. This research is a quantitative research. The population of this research is all teachers in TK Kapanewon Sewon totaling 100 teachers. Validity test using product moment correlation and reliability test using Cronbach's Alpha. Test requirements analysis using normality test, linearity test, and multicollinearity test. Hypothesis testing using multiple regression analysis. The results of this study were obtained jointly with the development of school supervisors, principal leadership, infrastructure and work motivation had a very significant positive influence on the performance of the teachers of Kapanewon Sewon Kindergarten. There is a significant positive effect on the understanding of School Superintendents' Guidance on the performance of TK Kapanewon Sewon teachers with an Effective Contribution (SE) of 13% and a Relative Contribution of 18.9% and a Total Effect (ET) of 33% and with an Indirect Effect of 10.1%. There is a significant positive effect of principal's leadership on the performance of TK Kapanewon Sewon teachers with an Effective Contribution (SE) of 21% and a Relative Contribution of 29.9% and a Total Effect (ET) of 53.4% and an Indirect Effect of 22.3%. There is a significant positive effect of infrastructure on the performance of TK Kapanewon Sewon Kindergarten teachers with an Effective Contribution (SE) of 12% and a Relative Contribution of 16.9% and a Total Effect (ET) of 32.6% and with an Indirect Effect of 11.7%.